2020
DOI: 10.1016/j.ijsu.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on surgical residency programs in Pakistan; A residents' perspective. Do programs need formal restructuring to adjust with the “new normal”? A cross-sectional survey study

Abstract: Background: Due to high-risk exposure of surgical residents to coronavirus, surgical residency programs have changed their training methods and working hours drastically. The purpose of this study is to find out the positive and negative impacts of the pandemic on surgical residency programs and on the lives of surgical residents. Materials and methods: A cross-sectional study was conducted on 112 surgical residents of a tertiary care hospital in Pakistan, with a mean age of 30.5 years from all the departments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 18 publications
7
75
0
Order By: Relevance
“…All 5 of the orthopaedic training programmes in the United States surveyed by An et al had restructured rotas to include periods of clinical duty followed by remote work and self-isolation [ 31 ]. Five studies reported a reduction in trainee presence within the hospital [ 17 , 22 , 23 , 26 , 32 , 33 ]. Ninety-two percent (60/65) of United States urology programs reported a formal reduction of trainee presence, with a significant decrease in patient-contact time from an average of 4.7 days per week to 2.1 ( p < 0.001) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All 5 of the orthopaedic training programmes in the United States surveyed by An et al had restructured rotas to include periods of clinical duty followed by remote work and self-isolation [ 31 ]. Five studies reported a reduction in trainee presence within the hospital [ 17 , 22 , 23 , 26 , 32 , 33 ]. Ninety-two percent (60/65) of United States urology programs reported a formal reduction of trainee presence, with a significant decrease in patient-contact time from an average of 4.7 days per week to 2.1 ( p < 0.001) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-three percent of 1102 general surgery trainees reported increased burnout compared to before the pandemic [ 17 ]. Only 1 study reported an improvement in mental health during the pandemic: a Pakistani study across all surgical specialities found that burnout was significantly reduced compared to pre-pandemic ( p < 0.001) [ 32 ]. This may be due to a significant reduction in working hours.…”
Section: Resultsmentioning
confidence: 99%
“…These challenges faced by orthopedic residents is echoed by residents in other surgical specialties, with many surgical residents being unable to keep up with surgical and clinical exposure due to the dwindling elective surgery rate and clinic attendance numbers. 27 , 30 Whilst some governing bodies overseeing the training of residents, such as the Accreditation Council for Graduate Medical Education (ACGME), have adapted their administrative requirements of training, such that the reduced clinical exposure of residents does not impact their ability to receive their eventual specialist accreditation, it remains to be seen whether this reduction in exposure will affect the clinical competency of future specialists trained during this pandemic era. The ACGME system of postgraduate education accreditation originated from the United States of America, and has since expanded internationally, with the system currently being employed in Singapore, Qatar, the UAE, and Saudi Arabia, amongst other countries, with the system replacing previously instituted postgraduate accreditation programs.…”
Section: Discussionmentioning
confidence: 99%
“…12 Trainees in other specialties have similarly expressed personal concern of acquiring and transmitting COVID-19 to family members. [13][14][15][16] Part of the COVID-19-related anxiety is likely associated with the uncertainty of the pandemic's future course. While many practices have now resumed average clinical volumes, 17 there is continued fear of the pandemic's effect on future surgical caseloads, job prospects, and continued exposure risks.…”
Section: Discussionmentioning
confidence: 99%
“…While this survey assesses the impact to ophthalmology residents in particular, other surgical specialties have experi-enced similar changes to training volumes and resident wellbeing. 14,19,20 There will continue to be future unavoidable decreases to clinical and surgical volumes due to COVID-19, and it is important for residency training programs to understand the potential impact to this future generation of surgeons and to prepare accordingly. Most importantly, we must prioritize trainee safety by enforcing PPE guidelines and minimizing known COVID-19 exposure as much as possible.…”
Section: Discussionmentioning
confidence: 99%